Platelet Collagen Receptors - Clemetson, Kenneth J.; Clemetson, Jeannine M. (Thrombosis and Haemostasis, 2001)
Collagens are important platelet activators in the vascular subendothelium and vessel wall. Since the regulation of platelet activation is a key step in distinguishing normal haemostasis from pathological thrombosis, collagen interactions with platelets are important targets for pharmacological control. Platelets have two major receptors for collagens, the integrin α2 β1, with a major role in adhesion and platelet anchoring and the Ig superfamily member, GPVI, principally responsible for signalling and platelet activation. In addition, GPIb-V-IX, can be considered as an indirect collagen receptor acting via von Willebrand factor as bridging molecule and is essential for platelet interactions with collagen at high shear rates. There is some evidence for additional receptors, which may regulate the response to individual collagen types. This review discusses how these receptors work separately with specific agonists and proposes possible mechanisms for how they work together to regulate platelet activation by collagen, which remains controversial and poorly understood.
Keywords: Platelet; receptor; collagen; integrin; Ig superfamily